Political - economic analysis of free-trade agreements. - LEVY, Philip I. (1997)
Demonstrates that bilateral free-trade agreements can undermine political support for further multilateral trade liberalization. Points out that if a bilateral trade agreement offers dis-proportionately large gains to key agents in a country, then their reservation utility is raised above the multilateral free-trade level, and a multilateral agreement would be blocked.